2021
DOI: 10.1186/s12879-020-05699-9
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter cloacae infection of the shoulder in a 52-year-old woman without apparent predisposing risk factor: a case report and literature review

Abstract: Background Enterobacter cloacae (E. cloacae) is one of the commensal flora in the human intestinal tract and a prevalent nosocomial pathogen, which rarely causes infectious osteoarthritis in immunocompetent patients without recent trauma or surgery. Here, we report the first case of septic monoarthritis of the shoulder caused by E. cloacae in an immunocompetent patient. Case presentation A 52-year-old female with a 6-year history of right shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Similarly, although we identified all E. cloacae as MDR isolates, they were previously reported with a low frequency (7.1%) in milk samples from Egypt in 2011 ( Ahmed and Shimamoto, 2011 ). However, they were recently detected in human samples ( Huang et al, 2021 ), which in turn emphasizes again the concept of transferring between animal/animal products including milk from/to human and animal during these 10 years. Alternatively, MDR K. pneumoniae isolates were widely detected in milk samples ( Yang et al, 2020 ) and this is concordant with what was reported in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, although we identified all E. cloacae as MDR isolates, they were previously reported with a low frequency (7.1%) in milk samples from Egypt in 2011 ( Ahmed and Shimamoto, 2011 ). However, they were recently detected in human samples ( Huang et al, 2021 ), which in turn emphasizes again the concept of transferring between animal/animal products including milk from/to human and animal during these 10 years. Alternatively, MDR K. pneumoniae isolates were widely detected in milk samples ( Yang et al, 2020 ) and this is concordant with what was reported in our study.…”
Section: Discussionmentioning
confidence: 92%
“…This was the case of a 52-year-old female with infected arthritis of the right shoulder, whose joint aspirate culture showed a cefazolin-resistant E. cloacae. She was treated with levofloxacin, and she stopped experiencing shoulder swelling and severe pain [31]. Precisely, because sometimes there are few therapeutic options available to treat infections, in vitro studies using essential oils from plants have shown to have activity against multidrug-resistant Enterobacteriaceae isolates [32,33], which would be a basis for the development of new and effective antibacterial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a more virulent species, E. cloacae [ 29 ], was involved in several cases. The isolated organism was reported to be a commensal organism of the gastrointestinal tract, rather than the ocular surface [ 30 ], and it can also be found in soil and plants. It therefore was no surprise that the cases in which E. cloacae was identified were caused by wooden sticks.…”
Section: Discussionmentioning
confidence: 99%